Perencanaan Jaringan Pipa Sistem Penyaluran Air Buangan Terpusat (Off-Site System) di Kecamatan Pasar Jambi, Kota Jambi - Monik Kasman; Hadrah Hadrah; Robby Ikhsan (Jurnal Daur Lingkungan, 2020)
Improving the quality of service and processing of infrastructure and facilities for wastewater has been programmed in the national development program 2000-2004 as stated in Law No. 25 of 2000. For this reason, the need for waste management and treatment to minimize environmental pollution, one of which is liquid waste generated from the community in the form of wastewater, centralized wastewater pipeline planning in Pasar Kecamatan, Jambi City, as an illustration or engineering in environmental management especially wastewater, because this area is dense with buildings and settlements, making it feasible to build a wastewater distribution pipeline system. Based on the analysis in this plan, the total number of service blocks for Jambi Market District consists of 11 service blocks with coverage in 4 Kelurahan, namely Beringin kelurahan with 3 service blocks, Orang Kayo Hitam Subdistrict 3 service blocks, Sungai Asam with 3 service blocks, and Pasar Jambi 2 service blocks, for the total pipe needs, the total number of lateral pipes is 61 pipes with a total length of 6579.2 m, for the total branch pipes are 17 pipes with a total length of 5801 m, and for the main pipe consists of 10 main pipes to drain water discharge to WWTP, totaling 10 main pipes with a total length of 2075, the diameter on the market from the smallest is 90 mm and the largest is 800 mm. Complementary buildings consist of clean out as many as 134 clean out terminals, 80 manholes, 2 pumps, and 1 siphon or crossing building, minimum digging depth for lateral pipes is 0.88 m and the deepest follows the ground slope or assuming with requirement if the ground pipe slope is less than 0, the final drainage of each pipe meets the drainage standard that is 0.6 m / sec <Vp <3 m / sec.